The Potential Roles of RNA N6-Methyladenosine in Urological Tumors - Li, Yang; Ge, Yu-zheng; Xu, Luwei; Xu, Zheng; Dou, Quanliang; Jia, Ruipeng (Frontiers in Cell and Developmental Biology, 2020)
N6-methyladenosine (m6A) is regarded as the most abundant, prevalent and conserved internal mRNA modification in mammalian cells. M6A can be catalysed by m6A methyltransferases METTL3, METTL14 and WTAP (writers), reverted by demethylases ALKBH5 and FTO (erasers), and recognized by m6A -binding proteins such as YTHDF1/2/3, IGF2BP1/2/3 and HNRNPA2B1 (readers). Emerging evidence suggests that m6A modification is significant for regulating many biological and cellular processes and participates in the pathological development of various diseases, including tumors. This article reviews recent studies on the biological function of m6A modification and the methylation modification of m6A in urological tumors.